DESIGN PROCEDURE FOR MAKING AND REPAIRING COMPOSITE SANDWICH BASED ON AUGMENTED REALITY - Irvan Nur Hanafi; Lilies Esthi Riyanti; Hari Kurniawanto (EDUTECH, 2022)
Composite-based structures are becoming increasingly common in aircraft construction. Its use is done to improve structural strength performance and weight loss of aircraft. Composite is divided into two manufacturing concepts, namely, composite sandwich and also composite laminate. The composite sandwich concept provides a method for obtaining high bending stiffness with minimal weight compared to laminate construction. The number of advantages obtained in composite sandwiches can’t be separated from the level of difficulty possessed in the process of making and repairing composites. This study examines the hazards caused in the manufacturing and repair procedures using the Job Hazard Analysis method. The concept and design of the procedure after analysis will be implemented into an augmented reality-based education system using blender and unity applications.